Three-dimensional imaging system based on a light-emitting diode array - Son, Jung-Young; Saveljev, V. V.; Kim, Dae-Sik; Kwon, Yong-Mu; Kim, Shin-Hwan (SPIE-SOC PHOTO-OPTICAL INSTRUMENTATION ENGINEERS, 2007)
A two-dimensional light-emitting diode array is used to replace the viewing-zone-forming optics in-multiview full-parallax three-dimensional image display systems. Since the array is not working merely as the viewing-zone-forming optics but also as the backlight panel for the liquid-crystal display (LCD) panel, it allows constructing three-dimensional imaging systems having the same structure as the current LCD display. The designed system displays images with good depth sense. (C) 2007 Society of Photo-Optical Instrumentation Engineers.